Synthesis and characterisation of CaO-xSrO catalyst for production of palm-based trimethylolpropane triesters - Tan, Ivan Choon Tah (2017)
Presently, interest on development of plant-based lubricant or biolubricant is increasing. This is due to its biodegradable property, renewable and non-toxicity when compared to mineral oil-based lubricant. The focus of this study was to synthesise calcium oxide mixed with strontium oxide (CaO•xSrO) where x is different composition of strontium oxide calculated based on the weight of calcium oxide as heterogeneous mixed metal oxides base catalysts. The catalyst (CaO•xSrO) was synthesised using wet impregnation technique. The synthesised catalysts were then characterised by X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), scanning electron microscopy with energy dispersive X-ray microscopy (SEM/EDX) and temperature-programmed desorptionof carbon dioxide (TPD-CO2). From the characterisations, catalysts synthesised (CaO•xSrO) shown to have high basic strength when SrO was impregnated on CaO besides providing alternate basic site to the synthesised catalyst (CaO•xSrO). The XRD and SEM-EDX data also showed that SrO on CaO was successfully synthesised with the detection of composition of SrO element using both XRD and SEM-EDX instrument. The synthesised CaO•xSrO catalysts were used to synthesis trimethylolpropane triesters (TMPTE) by transesterification of trimethylolpropane (TMP) and palm oil methyl esters (POME) to yield the product of TMPTE. TMPTE was deemed as a potential biolubricant base stock due to its excellent lubricity, viscosity–temperature characteristics, and low volatility. The synthesised product of TMPTE was analysed by gas chromatography - flame ionization detector (GC-FID) and fourier transform infrared (FTIR) for compositional study and functional group study respectively. The optimum conditions were obtained with 240 minutes reaction time using CaO•5SrO as catalyst, reaction temperature of 180oC, 1 %w/w catalyst loading to weight of POME and TMP, 6:1 of POME/TMP molar ratio at a fixed vacuum pressure of 2.5 mbar. The yield of final product (TMPTE) was found out to be 88.5% using the optimum conditions stated.